2017
DOI: 10.1155/2017/8953829
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Isolates and Their Antimicrobial Susceptibility Patterns of Wound Infections among Inpatients and Outpatients Attending the University of Gondar Referral Hospital, Northwest Ethiopia

Abstract: Background. The widespread uses of antibiotics, together with the length of time over which they have been available, have led to the emergence of resistant bacterial pathogens contributing to morbidity and mortality. This study was aimed to assess bacterial isolates and their drug susceptibility patterns from inpatients and outpatients with pus and/or wound discharge. Methods. A cross-sectional study was conducted at the University of Gondar Referral Hospital from March to May, 2014. Wound swab samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

31
92
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(140 citation statements)
references
References 18 publications
31
92
17
Order By: Relevance
“…The higher incidence of S. aureus (54.1%), K. pneumoniae (20.8%) and E. coli (8.3%) are reported in an Indian study 23 . An Ethiopian study reported 28.7% S. aureus, 12.5% Klebsiella, 11.8% coagulasenegative Staphylococci, 11% Citrobacter, 9.6% Enterobacter, 5.9% each of the P. aeruginosa and E. coli and 4.4% Proteus which is contrary to the finding of the present study 20 . The results of a Nigerian study also reported predominantly S. aureus (38%) in wound infections followed by P. aeruginosa (18.7%), Klebsiella (17%), which differ in frequencies reported in the current study 24 .…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The higher incidence of S. aureus (54.1%), K. pneumoniae (20.8%) and E. coli (8.3%) are reported in an Indian study 23 . An Ethiopian study reported 28.7% S. aureus, 12.5% Klebsiella, 11.8% coagulasenegative Staphylococci, 11% Citrobacter, 9.6% Enterobacter, 5.9% each of the P. aeruginosa and E. coli and 4.4% Proteus which is contrary to the finding of the present study 20 . The results of a Nigerian study also reported predominantly S. aureus (38%) in wound infections followed by P. aeruginosa (18.7%), Klebsiella (17%), which differ in frequencies reported in the current study 24 .…”
Section: Discussioncontrasting
confidence: 99%
“…Most of the wounds are colonized with a single microbial growth, but some cases of wound infection may have polymicrobial growth. A polymicrobial etiology was observed in cases of pediatric wound infections in this study, which is closer to the polymicrobial growth reported by an Ethiopian study 20 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations